Steroids for intubated croup masking airway haemangioma. Issue 1 (January 1996) - Kiff, K M; Mok, Q; Dunne, J; Tasker, R C
Abstract : Recently, the beneficial role of steroids for acute laryngotracheobronchitis has been more clearly defined for both intubated and unintubated patients. However, corticosteroids also improve the clinical signs of airway haemangiomata. Two patients are described who illustrate how this can be a source of diagnostic confusion.